Buddhist women across cultures: realizations - Karma Lekshe Tsomo (SUNY series, feminist philosophy, 1999)
Mahāprajāpatī's legacy : the Buddhist women's movement : an introduction / Karma Lekshe Tsomo -- The female in Buddhism / Elizabeth J. Harris -- Buddhist women in India and precolonial Sri Lanka / Lorna Dewaraja -- Restoring the order of nuns to the Theravādin tradition / Senarat Wijayasundara -- The red cord untied : Buddhist nuns in eighteenth-century China / Beata Grant -- Japanese Buddhist nuns : innovators for the sake of tradition / Paula K.R. Arai -- Can women achieve enlightenment? : A critique of sexual transformation for enlightenment / Hae-ju Sunim (Ho-Ryeon Jeon) -- Tibetan Buddhist women practitioners, past and present : a garland to delight those wishing inspiration / Janice D. Willis -- Pregnancy and childbirth in Tibetan culture / Sarah Pinto -- Change in consciousness : women's religious identity in Himalayan Buddhist cultures / Karma Lekshe Tsomo -- Conception and the entry of consciousness : when does a life begin? / Cait Collins -- East, West, women, and self / Anne C. Klein -- Appropriate treasure? : Reflections on women, Buddhism, and cross-cultural exchange / Sara Shneiderman -- Comparing Buddhist and Christian women's experiences / Karma Lekshe Tsomo -- Aung San Suu Kyi : a woman of conscience in Burma / Theja Gunawardhana -- A model for laywomen in Buddhism : the Western Buddhist Order / Dharmacharini Sanghadevi -- Feminism, lay Buddhism, and the future of Buddhism / Rita M. Gross -- Epilogue / Karma Lekshe Tsomo.